Herzinsuffizienz – ein Modell für Multimorbidität - Güder, Gülmisal; Ertl, Georg (DMW - Deutsche Medizinische Wochenschrift, 2017)
Heart failure frequently is the consequence of different cardiac diseases and is associated with multiple cardiac and non-cardiac co-morbidities. It may be exemplary for multi-morbidity in the elderly, has negative impact on various organ systems and may induce further comorbidities. The following article addresses heart failure as a multisystem disorder.
Keywords: Herzinsuffizienz; Komorbidität; Multimorbidität; Medikamenteninteraktion